Research in the Auditor's Opinion Formulation Process: State of the Art. - Felix, William L.; Kinney, William R. (The Accounting Review, 1982)
ABSTRACT: This paper reviews auditing research on the process by which auditors form their opinions on financial statements. A structure for this research is provided to organize the review and to provide insights into areas where research is needed. This structure is obtained by cross-classifying steps in theory development and steps in the opinion formulating process. While several important lines of research have begun, the primary conclusion is that a great deal of potentially important research has not been performed.